2013
DOI: 10.3399/bjgp13x673702
|View full text |Cite
|
Sign up to set email alerts
|

Employment loss during economic crisis and suicidal thoughts in Belgium: a survey in general practice

Abstract: BackgroundThe economic crisis of 2009 led to a wave of corporate reorganisations and bankruptcies, with many dismissals of employees. GPs were confronted with subsequent health consequences. AimTo assess the possible relationship between losing one's job and having suicidal thoughts. Design and settingA survey of patients aged 18-49 years recruited from GP practices in Belgium in Deurne (Flemish region) and La Louvière (Walloon region) from September to December 2010. MethodAnonymous self-administered question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 19 publications
1
15
0
2
Order By: Relevance
“…There is a positive association between unemployment and depression (Economou et al, 2012;Riumallo-Herl et al, 2014;Tefft, 2011), suicidal thoughts (Vanderoost et al, 2013) and complete suicide (Costa et al, 2012;Duleba et al, 2012;Uutela, 2010). Our results add to these findings and suggest that unemployment or loss of income is associated with an overall 20.0% increase in MDD relapse.…”
Section: To the Editorsupporting
confidence: 79%
“…There is a positive association between unemployment and depression (Economou et al, 2012;Riumallo-Herl et al, 2014;Tefft, 2011), suicidal thoughts (Vanderoost et al, 2013) and complete suicide (Costa et al, 2012;Duleba et al, 2012;Uutela, 2010). Our results add to these findings and suggest that unemployment or loss of income is associated with an overall 20.0% increase in MDD relapse.…”
Section: To the Editorsupporting
confidence: 79%
“…Another study reported that the financial crisis in Spain has been associated with an increase in suicides , and this study indicated that the financial crisis may be linked to an increased risk of suicide, particularly among men and individuals of working age. A survey of individuals aged from 18 to 49 in Belgium suggested that losing one's employment over the previous year was definitely associated with suicidal thoughts . We suggested in a previous study that stock prices were associated with the suicide rate among men .…”
mentioning
confidence: 77%
“…Takahashi (6) reported that there were multiple risk factors for suicide, such as "previous suicide attempts", "a history of a psychiatric disorder", "a lack of support", and "experience of loss" (economic loss, loss of position, etc.). Some studies have examined the association between various economic factors and suicide (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Studies in Japan have reported that the unemployment rate and suicide rate were correlated (7,8).…”
mentioning
confidence: 99%
“…A second methodological problem is how to measure (mental) health. We found many different ways to measure mental health, among which are surveys on mental disorders/suicidal thoughts in a primary care setting 27 , 28 or secondary data analysis (health interview surveys). Rihmer et al looked at annual antidepressant consumption, which can be seen as a possible proxy for the availability of psychiatric services and the treatment of depression, which is the most powerful predictor of suicide at the individual level.…”
Section: Methods Used To Measure Changes In Psychological Distress Dumentioning
confidence: 99%